(untitled) (International Journal of Engineering and Computer Science, 2017)
Wireless technology is growing very fast these days. Until very recently, wired network was needed to get online. Even wired telephones are becoming a thing of past. Mobile networks have evolved tremendously in last 4 decades [1]. Cellular concept was introduced with 1G (‘G’ stands for generation) networks. Today, 4G technology is getting ready to storm the markets and research on 5G has begun. Mobile communication is continuously one of the hottest areas that are developing at a booming speed, with advanced techniques emerging in all the fields of mobile and wireless communications.5G communication systems are being developed to solve the various problems the current communication systems (3G, 2.5G) are facing.4G & 5G will be an intelligent technology that will reduce the number of different technologies to a single global standard. This paper gives evolution of mobile wireless communication networks-1G to 5G how they are different from each other what advantages and disadvantages they have.